Antioxidant protective effect of Nelumbo nucifera extract against spermatogenic cells in male mice due to 2-methoxyethanol exposure - Badriatul Musyarofah; Putri Ayu Ika Setiyowati; Angella Ananda Syaputra; Amelia Kartika Reza; Yunita Ainul Khasanah; Rofiatun Solekha (Jurnal Teknologi Laboratorium)
One of the causes of infertility in men is influenced by the compound 2-Methoxyethanol (2-ME) that can increase Reactive Oxygen Species (ROS) which can distrub spermatogenesis. This study aimed to analyze the effect of antioxidant of Nelumbo nucifera extract on the histology of mice testicular spermatogenic cells. Male mice are divided into 6 groups. The negative control group (KN) was given distillated for 28 days ad libitum. The positive control group (KP) was injected subcutaneous (s.c) with 2-ME dose 200 mg/kg bw as much as 0.05 ml/ day for 7 days,  the drug group (KO) was injected s.c with 2-ME (200 mg/kg bw) as much as 0.05 ml/ day for 7 days and then injected s.c with Clomiphene citrate with a dose 50 mg/kg bw as much as 0.2 ml/ day for 21 days. The treatment group (P1, P2, P3) was injected s.c with 2-ME (200 mg/kg bw) as much as 0.05 ml/ day for 7 days and injected s.c with N. nucifera extract at low dose 50 mg/kg bw (P1), medium dose 150 mg/kg bw (P2), and high  dose 450 mg/kg bw (P3) as much as 0.2 ml/ day for 21 days. At the end of the study all mice were sacrificed and testicular collection was carried out. Testicular tissue was processed using Hematoxylin-Eosin staining and observed spermatogenic cells (spermatogonia, spermatocytes and spermatids). Data analysis using ANOVA test and advanced test Post hoct test. The results showed that there was a significant difference (p < 0.05) in number of spermatogenic cells of mice testicles between the negative group (KN), positive group (KP) and treatment group (P1, P2, P3). The optimal dose of N. nucifera extract that is most able to repair testicular tissue damage is a high dose.